Cannabidiol combined with GABAergic drugs but not with sodium channel blockers prevents the development of drug-resistance seizures in a preclinical model - Fuentes Mejia, Monserrat (2025)
Drug resistance affects 30% of patients with epilepsy. Cannabidiol (CBD)decreases the expression of drug-resistant seizures in specific syndromes.However, it is unknown if CBD prevents the development of drug-resistantcondition in epilepsy. This research was conducted to investigate ifsubchronic administration of CBD with sodium channel blockers modifies themortality associated with clonic-tonic seizures and the development of the drug-resistant phenotype induced by subchronic administration of 3-mercaptopropionic acid (3-MP) in rats. These effects were compared withthose elicited by antiseizure medications acting on the GABAA receptors. MaleWistar rats were used to evaluate CBD combined with different antiseizuremedications (phenobarbital, diazepam, valproic acid, lamotrigine andoxcarbazepine) during the repetitive administration of 3-MP. The mortalityrate and development of drug-resistant seizures were estimated.Computational experiments explored interactions between CBD and sodiumchannel blockers in the NaV1.7 receptor. Subchronic administration of CBD alonedid not modify neither the mortality rate nor the development of drug-resistantseizures. CBD combined with phenobarbital or diazepam reduced the mortalityrate and prevalence of drug-resistant seizures. In contrast, coadministration ofCBD with valproic acid or lamotrigine did not modify neither the mortality rate northe expression of drug-resistant seizures. Contrariwise, combining CBD withoxcarbazepine at ED50 increases the incidence of drug-resistant seizures.Computational experiments suggested that CBD acting on NaV1.7 interfereswith the action of sodium channel blockers and precludes their inhibitoryeffects. Our results indicate that repeated administration of CBD withGABAergic antiseizure medications, but not sodium channel blockers,decreases the mortality and prevents the development of the drug-resistantphenotype induced by repeatedly provoked severe seizures.